Complete androgen insensitivity syndrome associated with bilateral sertoli cell adenomas and unilateral paratesticular leiomyoma: A case report - Savaş-Erdeve, Şenay; Aycan, Zehra; Keskin, Melikşah; Çetinkaya, Semra; Karaman, Ayşe; Apaydın, Sema; Çakmakçı, Emin (The Turkish Journal of Pediatrics, 2016)
Complete androgen insensitivity syndrome (CAIS) disorder of sex development due to mutations that cause function loss in androgen receptors in 46, XY individuals. The risk of malignancy in CAIS is 5-10% until the age of 25 years. A 17-year-old patient raised as a female presented to our clinic complaining of amenorrhea. She had a history of surgery for inguinal hernia at the age of 2 years. The patient's niece of the same age had been diagnosed with CAIS at our department and gonadectomy had been performed six months ago. She had four other nieces with the same diagnosis. Her external genital appeared phenotypically female. On physical examination, breast development was Tanner stage 5 and pubic hair Tanner stage 2 with scarce axillary hair. The gonad was palpated in the left inguinal region. Chromosome analysis revealed 46, XY and sex determining region Y (SRY) was positive. The patient was diagnosed as CAIS with laboratory and radiology results. The Sexual Orientation and Gender Identity Committee decided on gonadectomy. Histopathological evaluation of the gonad revealed bilateral Sertoli cell tumor and right paratesticular leiomyoma.
Keywords: complete androgen insensitivity syndrome; sertoli cell adenoma; sex differentiation